Long Term Lean Implementation: A Case Study At Job Shop Production Organisation In Malaysia - Samad, Mohd Surhardi Effandy Abd (2022)
The purpose of this qualitative case study is to understand the management of soft side of organisational approach to Lean implementation and the impact on long term operational performance in a job shop production oriented manufacturing organisation in Malaysia. The objective of this study was to explore the factors that hinder the long established Lean implementation from retaining competitive performance of job shop organisation in the long run. The case issue of the one selected organisation for this study is that the Lean implementation implemented since the early of 2000s has not been able to support the job shop organisation to retain competitive performance for the long term. The results of the thematic analysis have identified 3 overarching themes namely fade of routine engagement, inadequate assets viability and shift in operating measures. Finally, the themes obtained give the meaning that the operational resources competencies for the organisation no longer competent to retain previous performance and also contribute to the improvement of operational performance for the long run. This study provides an in-depth understanding through direct experience of the operational perspective on long term Lean implementation especially in the job shop production environment. The findings obtained from this study are subjected to context of the study and application of methodology and are not intended to be generalized to other industries.